Phenotypic and Genotypic Features of Thai Patients With Nonsyndromic Tooth Agenesis and WNT10A Variants - Kanchanasevee, Charinya; Sriwattanapong, Kanokwan; Theerapanon, Thanakorn; Thaweesapphithak, Sermporn; Chetruengchai, Wanna; Porntaveetus, Thantrira; Shotelersuk, Vorasuk (Frontiers in Physiology, 2020)
Tooth agenesis is one of the most common orodental anomalies with phenotypic and genotypic heterogeneity. Its prevalence ranges from 2.5% to 7%. Of nonsyndromic tooth agenesis (NSTA), mutations in WNT10A have been proposed to be its most common cause. This study aimed to characterize dental features and genetic variants of NSTA in a Thai population. We recruited 13 unrelated patients with NSTA who attended the Faculty of Dentistry, Chulalongkorn University, Thailand between 2017 and 2019. All 13 underwent whole exome sequencing which successfully identified likely pathogenic genetic variants, all in WNT10A, in five patients. All five patients had agenesis of second premolars, while three had absent or peg-shaped upper lateral incisors. Patient 1 possessed a novel heterozygous duplication, c.916_918dupAAC (p.Asn306dup) in WNT10A. Patients 2 and 3 harbored the heterozygous and homozygous c.637G>A (p.Gly213Ser) in WNT10A, respectively. Patients 4 possessed the heterozygous c.511C>T (p.Arg171Cys) in WNT10A. Patient 5 harbored both the homozygous c.511C>T (p.Arg171Cys) in WNT10A and a novel heterozygous c.413A>T (p.Asn138Ile) in EDARADD, suggesting digenic inheritance. We then studied dental and genetic features of 10 more family members of these five patients. WNT10A variants were found in 7 members but only 3 had NSTA, suggesting 67% penetrance (8 affected/12). Frequencies of the c.511C>T in our in-house 1,876 Thai exome database, Asian populations, and non-Asian populations were 0.016, 0.005-0.033, and 0.001, respectively; while those of the c.637G>A were 0.016, 0.004-0.029, and 0.000, respectively. In conclusion, our study reports two novel variants with one each in WNT10A and EDARADD, expanding genotypic spectra of NSTA. Agenesis of second premolars is a common phenotype of affected individuals with variants in WNT10A; however, its penetrance is incomplete. Lastly, the different frequencies of WNT10A variants, c.511C>T and c.637G>A, in diverse populations might contribute to the prevalence range of NSTA across continents.